New insights into the catalytic mechanism of vitamin K epoxide reductase (VKORC1) – The catalytic properties of the major mutations of rVKORC1 explain the biological cost associated to mutations. Issue 1 (16th February 2013) - Matagrin, Benjamin; Hodroge, Ahmed; Montagut-Romans, Adrien; Andru, Julie; Fourel, Isabelle; Besse, Stéphane; Benoit, Etienne; Lattard, Virginie
Abstract : The systematic use of antivitamin K anticoagulants (AVK) as rodenticides caused the selection of rats resistant to AVKs. The resistance is mainly associated to genetic polymorphisms in the Vkorc1 gene encoding the VKORC1 enzyme responsible for the reduction of vitamin K 2, 3‐epoxide to vitamin K. Five major mutations, which are responsible for AVK resistance, have been described. Possible explanations for the biological cost of these mutations have been suggested. This biological cost might be linked to an increase in the vitamin K requirements. To analyze the possible involvement of VKORC1 in this biological cost, rVKORC1 and its major mutants were expressed in Pichia pastoris as membrane‐bound proteins and their catalytic properties were determined for vitamin K and 3‐OH‐vitamin K production. In this report, we showed that mutations at Leu‐120 and Tyr‐139 dramatically affect the vitamin K epoxide reductase activity. Moreover, this study allowed the detection of an additional production of 3‐hydroxyvitamin K for all the mutants in position 139. This result suggests the involvement of Tyr‐139 residue in the second half‐step of the catalytic mechanism corresponding to the dehydration of vitamin K epoxide. As a consequence, the biological cost observed in Y139C and Y139S resistant rat strains is at least partially explained by the catalytic properties of the mutated VKORC1 involving a loss of vitamin K from the vitamin K cycle through the formation of 3‐hydroxyvitamin K and a very low catalytic efficiency of the VKOR activity.